Deep learning to infer eddy heat fluxes from sea surface height patterns of mesoscale turbulence - Tom M. George (Nature Portfolio, 2021)
Eddy heat fluxes crucially affect large-scale oceanic currents but are challenging to monitor on a global scale. Here the authors develop a Deep Learning model to predict the eddy heat fluxes from sea surface height data only, bypassing the need for simultaneous observations of the deep ocean.